2017
DOI: 10.1002/1873-3468.12702
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptors link lipid metabolism and inflammation

Abstract: The response of immune cells to pathogens is often associated with changes in the flux through basic metabolic pathways. Indeed, in many cases changes in metabolism appear to be necessary for a robust immune response. The Liver X receptors (LXRs) are members of the nuclear hormone receptor superfamily that regulate gene networks controlling cholesterol and lipid metabolism. In immune cells, particularly in macrophages, LXRs also inhibit pro-inflammatory gene expression. This Review will highlight recent studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
155
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(167 citation statements)
references
References 117 publications
(192 reference statements)
0
155
0
2
Order By: Relevance
“…7 C ). Because several DEG are targets of the liver X receptor (LXR) (32), we sought to evaluate whether indole regulated the hepatic concentration of oxysterols that are key ligands for LXR. Interestingly, we found that among the panel of 10 oxysterols analyzed (Supplemental Table 4), the concentration of 4β-hydroxycholesterol was higher in the liver of mice treated with indole and LPS compared to mice treated with LPS alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7 C ). Because several DEG are targets of the liver X receptor (LXR) (32), we sought to evaluate whether indole regulated the hepatic concentration of oxysterols that are key ligands for LXR. Interestingly, we found that among the panel of 10 oxysterols analyzed (Supplemental Table 4), the concentration of 4β-hydroxycholesterol was higher in the liver of mice treated with indole and LPS compared to mice treated with LPS alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition , LXRα has anti-inflammatory activity through inhibition of NF-κB signaling pathway. 46 These above effects further support that MsrA has pleiotropic regulatory functions in HDL metabolism and inflammation, which largely relied on LXRα-upregulation.…”
Section: Discussionmentioning
confidence: 72%
“…It has been confirmed that ATP-binding cassette transporters, ABCA1 and ABCG5/8 are direct LXRα target genes. 46 Hepatic ABCA1 functions to export cellular cholesterol to lipid-free apoAI during the biogenesis of HDL, 47 and ABCG5 and ABCG8 form heterodimers that control biliary cholesterol secretion from the liver. 48 Our present study showed that MsrA expression promoted hepatic cholesterol efflux and excretion through the increase of ABCA1 and ABCG5/8 pathway, most probably due to the upregulation of LXRα.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression of OPN has been linked to coronary atherosclerotic lesions (Giachelli et al, 1993;Matsui et al, 2003;Ohmori et al, 2003), type 2 diabetes (Takemoto et al, 2000;Yamaguchi et al, 2004), and diabetic nephropathy (Hsieh et al, 2006;Kelly, Wilkinson-Berka, Ricardo, Cox, & Gilbert, 2002;Nicholas et al, 2010;Tachibana et al, 2012). Liver X receptors (LXRs) are ligand-dependent nuclear receptors that participate in cholesterol homeostasis and inflammatory signaling (de Wit, Vanmol, Kamermans, Hendriks, & de Vries, 2017;Schulman, 2017;Waddington, Jury, & Pineda-Torra, 2015). LXRs activate transcription via the binding of ligands either after heterodimerization with the retinoid X receptor (RXR) or another nuclear receptor after being activated by its own ligand (Jakobsson, Treuter, Gustafsson, & Steffensen, 2012).…”
mentioning
confidence: 99%